Galicia en el Real Decreto de 1916 - Méndez Fernández, Luz (Boletín de la Real Sociedad Geográfica, 2018)
En este artículo se analizan los cambios en la denominación de los ayuntamientos de Galicia causados por el Real Decreto de 1916. El objeto de este decreto era evitar que dos municipios tuviesen el mismo nombre. Se estudia la razón de cada caso de homonimia y se valora si el cambio era o no necesario así como la motivación de las nuevas formas impuestas. Finalmente, se describen brevemente los problemas que causó en el corpus toponímico gallego la castellanización antigua y frecuente de los nombres de lugar. Abstract This paper analyzes the changes in the denomination of the municipalities of Galicia, brought about the Royal Decree of 1916. The aim was to prevent two municipalities having the same name. In each case, the reason for this homonymy is studied and, in certain toponyms, it is determined whether or not there was a need for change, as well as the reasons for the new imposed forms. Finally we briefly describe some of the problems caused in the Galician toponymic corpus by early Castilianization and frequent occurrence.